Complete Chloroplast Genome Sequence of Chenopodium album from Northeastern India - Devi, Rajkumari Jashmi (Genome Announc, 2017)
Chenopodium album belongs to the complex genus Chenopodium of the family Amaranthaceae. It is an economically and medicinally important plant. We report here the first complete chloroplast genome sequence of C. album from northeastern India. This study shall add extensive information on the evolutionary relationships of the genus Chenopodium.